The Effect of Basil Leaves (Ocimum sanctum L.) as Natural Preservative for Mackerel (Rastrellinger sp.) - Rahmiati, Rahmiati; Nurtjahja, Kiki; Nasution, MHD. Fauzi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Basil is a plant that can be used as a traditional medicine. One part of the basil plant used as an alternative medicine is the leaves. Basil leaves contain active compounds, including flavonoids, saponins, tanins, and essensial oils. These active compounds is able to prevent the presence of pathogenic bacteria that can accelerate food spoilage, so that basil leaves can be used as an alternative natural preservative. The objective of the study was to determine the ability of basil leaves as a natural preservative forÂ  mackerel. The research was carried out in vitro, by observing the physical, chemical, and microbiological characteristicts of mackerel which were treated 8 hours of soaking basil leaf extract. Variations in the concentration of basil leaves used were 0, 25, 50, 75 and 100%. The results showed that the physical quality of the 8-hour storage samples showed changes in the physical quality of the fish, as seen from the color, eyes, gills, mucus, aroma and texture. The microbioloical quality of fish was analyzed by the total plate number method. The total number of bacteria decreased as the concentration of basil leaf extract increased